HCC Heterogeneity: Molecular Pathogenesis and Clinical Implications - Emilia Fransvea; Angelo Paradiso; Salvatore Antonaci; Gianluigi Giannelli (Cellular Oncology)
Background: Hepatocellular carcinoma (HCC) poses a major challenge because of the extreme variability of the clinical outcome, which makes it difficult to properly stage the disease and thereby estimate the prognosis. There is growing evidence that this heterogeneous clinical behavior is attributable to several different biological pathways. A novel approach to mapping these differences is by investigating the epigenetics associated with certain clinical aspects.